Prevalence and associated factors of tobacco use among higher secondary schools students, Butwal, Rupandehi. - Panthi, Mina (2018)
ABSTRACT: Several studies have reported that tobacco use is growing problem among school students. However, depth of information available about prevalence and associated factors of tobacco use is insufficient. So, this study was conducted to find out prevalence and associated factors of tobacco use among higher secondary school students. A descriptive cross sectional study was conducted among 462 students recruited from six higher secondary schools of Butwal, Rupandehi by using two stages random sampling technique. Data were collected by using pre-tested semi structured questionnaire from July 2 to 28, 2017. The obtained data was entered in Epi info 3.2 and analyzed in Statistical Package for Social Science (SPSS) of version 16. Both descriptive (mean, median mode and range) and inferential statistic (Chi square) was used. Study found that prevalence of ever and current use of tobacco was 45.2% and 30.1% respectively. Hookah (62.2%) was predominantly use of tobacco followed by cigarettes smoking. The mean age of initiation of tobacco was 15 ± 2.03 SD. The common reasons of tobacco use were curiosity (49.3%), peer pressure (34%) and imitation of others (23.4%) and reasons for subsequent use were feel more relaxed (55.4%) and out of boredom (27.3%). Study also found that current use of tobacco was significantly associated with age (p=0.32), sex (p<0.001), school (p=0.003), number of friends in close circle (p<0.001, friends tobacco use (p<0.001, sibling and parental tobacco use (p<0.001) and awareness about the harmful effects of tobacco use (p=0.006). This study concluded that the prevalence of tobacco use among students is high. Several factors were associated with tobacco use. So, school curriculum should incorporate lessons on tobacco prevention and the negative consequence of tobacco use to raise awareness among students is necessary.